2011
DOI: 10.1103/physrevc.84.044318
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study of proton-neutron pairing correlations in the nuclear shell model

Abstract: A shell-model study of proton-neutron pairing in 2p1f shell nuclei using a parametrized Hamiltonian that includes deformation and spin-orbit effects as well as isoscalar and isovector pairing is reported. By working in a shell-model framework we are able to assess the role of the various modes of proton-neutron pairing in the presence of nuclear deformation without violating symmetries. Results are presented for 44 Ti, 45 Ti, 46 Ti, 46 V, and 48 Cr to assess how proton-neutron pair correlations emerge under … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 10 publications
1
29
0
Order By: Relevance
“…Due to the mixed nature of the quartets, Eq. (6), the QM ground state (7) contains an isovector component |iv = (13) and, for N Q > 1, a mixed component with both isovector and isoscalar quartets. As all these components are not orthogonal to each other, it is not trivial to analyze their competition in the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the mixed nature of the quartets, Eq. (6), the QM ground state (7) contains an isovector component |iv = (13) and, for N Q > 1, a mixed component with both isovector and isoscalar quartets. As all these components are not orthogonal to each other, it is not trivial to analyze their competition in the ground state.…”
Section: Resultsmentioning
confidence: 99%
“…(10,11), expressed in terms of collective pairs. One can notice that QCM describes less well the pairing correlations energies as compared to QCM.…”
Section: Omentioning
confidence: 99%
“…The SU(4) pairing model is, however, not realistic enough because it neglects the role played by the spin-orbit force, which is crucial for the description of atomic nuclei. Various studies have shown that the spin-orbit force strongly hinders the proton-neutron pairing correlations in the ground and excited states of N = Z nuclei [10][11][12]. Yet, the majority of these studies do not discuss the types of correlations induced by the proton-neutron pairing in the presence of spin-orbit interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important degrees of freedom which compete with the pairing in N=Z nuclei are the quadrupole ones. It has been shown that a simplified model Hamiltonian which includes only the isovector pairing interaction and a quadrupolequadrupole force is able to give a realistic description of the essential features of N=Z nuclei [26,27] In the mean field version of this model the quadrupole degrees of freedom are commonly included in a deformed mean field and the isovector pairing is treated in the single-particle basis corresponding to it (e.g., see [28]) In what follows we use this framework to analyze the quartet correlations in deformed N=Z nuclei. As an illustration we consider the same nuclei shown in Table 1.…”
mentioning
confidence: 99%